RIGHTS AND OBLIGATIONS OF A HUSBAND AS A CIVIL SERVANT TO HIS EX-WIFE AFTER DIVORCE ACCORDING TO INDONESIAN LAW - Sirman Dahwal; Dimas Dwi Arso (Universitas Bengkulu, 2023)
This research was normative legal research in nature so the first stage that the authors did was collecting books and writings that were relevant to this research title to gather data and theory based on the problems of this research. These data were expected able to identify problems and explain the focus of the discussion. The discussion focused on material analysis related to the rights and obligations of a husband as a civil servant to his ex-wife after divorce according to Indonesian Law. Therefore, the objectives of this research are to find out 1) the rights and obligations of a husband as a civil servant to his ex-wife after divorce according to Indonesia Law, 2) the form of the implementation of rights and obligations of a husband as a civil servant itself, and 3) factors inhibiting the implementation of the rights and obligations. The method used to uncover and explain the problems was content analysis with normative, literal-historic, and empirical approaches. These approaches aimed to investigate the existence of the regulation of rights and obligations and to understand the true meaning of rights and obligations and whether the function of law has met a sense of justice, certainty, and benefits. The results revealed that the rights and obligations of a civil servant to his ex-wife have been regulated in the Indonesian Marriage Law which is under Law Number 1 of 1974 as amended by Law Number 16 of 2019 concerning Marriage and other related regulations such as the Compilation of Islamic Law. These rights and obligations are inherent in legal subjects, especially for civil servants, which must be carried out by the husband and respected by both parties. These rights consist of the right to hadhanah living, mut'ah living, iddah living, and madhiyah living. Keywords: Right and Obligation, Indonesian Law